Investor to state dispute settlement : a challenge for democracy, ethics, the environment, and the rule of law - Kelam, Ivica (Array, 2019)
Until recently, international trade agreements did not cause any public reaction and were considered irrelevant to everyday life. The experience of the existing international trade agreements from NAFTA, through TPP, to TTIP and CETA, which are in the process of negotiations or ratification, has shown that they have a huge impact on the daily lives of citizens and affect the entire society and economy. These agreements are negotiated and concluded by neglecting ethical principles, democratic procedures, and human rights, where only economic interests are taken into account. In this paper we will explore how these agreements undermine universal ethical principles and democratic standards through the ISDS mechanism, imposing the economic interest of large capital against the welfare of society, the individual, and the environment. We will refer particularly to the work of Alfred-Maurice de Zayas, the United Nations Independent Expert on the Promotion of a Democratic and Equitable International Order (also known as Special Rapporteur), who in his reports to the United Nations General Assembly and in media appearances fiercely criticises the ISDS mechanism and its implementation in agreements such as CETA and TTIP.